A case-study evaluating river rehabilitation alternatives and habitat heterogeneity using the hydromorphological index of diversity. Issue 1 (2nd January 2021) - Gostner, W.; Annable, W. K.; Schleiss, A. J.; Paternolli, M.
Abstract: Concurrent rehabilitation alternatives were evaluated for a 1900 m reach of the River Etsch in northern Italy using a recently developed Hydro Morphological Index of Diversity (HMID) model. HMID is a new tool enabling quantitative assessments of river restoration alternatives on ecologically relevant scales. The model is able to characterize both the spatial and temporal hydrodynamic variability, in relation to morphological characteristics, and thereby to assess the overall physical habitat variability imparted by different restoration alternatives. Three habitat alternatives were evaluated (boulder clusters, groynes, alternating bars) and compared to existing conditions where a prismatic channel exists. The placement of boulder clusters represented the simplest and cheapest option to implement but produced marginal improvements in the aquatic habitat. Installation of groynes resulted in moderate increases to spatial habitat variability, resulting in the largest capital investment. The introduction of alternating bars within a modestly increased channel width produced the greatest increase in physical habitat diversity and thus morphodynamic complexity while resulting in moderate capital investment construction costs compared to a full geomorphic restoration. The alternating bar rehabilitation alternative also supported the greatest habitat diversity and lowest variation in hydraulic conditions under low-flow conditions.